Conducta obstétrica en paciente 34 años con 21 semanas de embarazo y malformaciones fetales. - Panchano Martínez, Estefanía Alexandra (2023)
Congenital malformations are structural and functional defects produced in embryonic or fetal development, of various etiologies, some are preventable, so prenatal diagnosis is essential to determine prognosis and obstetric future. The causative agents of congenital defects can be genetic, environmental or by interaction of both. 10% of the malformations are attributed to environmental causes, 25% to genetic factors and 65% to unknown factors, probably of a multifactorial order. There are approximately 4000 forms of these anomalies, however, they are included in two large groups which are: structural and functional. It is for these reasons that malformations are positioned as one of the important causes of infant mortality, disabilities and also chronic diseases. Congenital anomalies affect approximately one in 33 newborns, causing 3.2 million disabilities each year, and it is estimated that approximately 270,000 newborns die during their first 28 days of life. While the intake of folic acid during and before pregnancy can significantly reduce the risk of malformations, including spina bifida, anencephaly and other heart defects. (tango, 2021). The development of the clinical case is based on a 34-year-old multiparous patient with 21 weeks of gestation due to FUM on 08/13/2020 with an intergenic period of 2 months, her last pregnancy ended in abortion, she does not refer to a Personal Pathological history of allergies, toxic and surgical , risk factors age, lack of prenatal check-ups, not having an adequate diet and their habitat, however there are several theories put forward since by means of ultrasound it was possible to show that the fetus had a fetal malformation of anencephaly was incompatible with life and termination of pregnancy by abortion. Through this research I want to encourage the importance of prenatal check-ups carried out early and month by month in order to identify risk factors that can endanger pregnancy and provide adequate obstetric conduct.